Ecological impact of ciprofloxacin on commensal enterococci in healthy volunteers. (4th March 2017) - de Lastours, Victoire; Maugy, Elena; Mathy, Vincent; Chau, Françoise; Rossi, Benjamin; Guérin, François; Cattoir, Vincent; Fantin, Bruno; ,
Abstract : Background: The ecological impact of ciprofloxacin on commensal enterococci is unknown. Methods: Forty-eight healthy volunteers received ciprofloxacin from day (D) 0 to D14; stools were collected on D7, D14 and D42. Fluoroquinolone-susceptible and -resistant enterococci (FQ-SE and FQ-RE) were detected and quantified by culture, and identified by MALDI-TOF MS. The relative abundance of FQ-RE over FQ-SE was determined. The genetic basis of fluoroquinolone resistance was deciphered by partial sequencing of gyrA and parC genes. Clonal relatedness was determined by random amplification of polymorphic DNA PCR. Clinical trial no.: NCT00190151. Results: Enterococci were carried by 47/48 (98%) subjects. Total counts were reduced during ciprofloxacin therapy (4.0 and 3.9 log cfu/g on D7 and D14 versus 5.9 log cfu/g before and 6.9 log cfu/g after treatment; P  < 0.05). Twenty-one out of 48 (44%) carried FQ-RE; among them, 21/21 carried Enterococcus faecium, 19 carried Enterococcus faecalis and 11 carried other species. Five out of 48 (10%) harboured FQ-RE (ciprofloxacin MIC >4 mg/L) before treatment (all E. faecium ), 6 on D7 (3 E. faecium and 3 E. faecalis ), 8 on D14 (4 E. faecium and 4 E. faecalis ) and 10 (21%) on D42 (9 E. faecium and 1 E. faecalis ). The relative abundance of FQ-RE increased from 44% on D0 to 73% and 75% on D7 and D14, respectively. No acquisition of fluoroquinolone resistance among endogenous D0 strains was evidenced. All (14/14) distinct Fluoroquinolone-resistant E. faecalis clones were gyrA / parC double mutants with high-level resistance (ciprofloxacin MIC >64 mg/L). In contrast, 34/35 E. faecium exhibited low-level resistance (ciprofloxacin MIC 4–32 mg/L) with no gyrA / parC mutation, but overexpressed the chromosomal Efm qnr gene. As compared with Fluoroquinolone-susceptible strains, Fluoroquinolone-resistant E. faecium were more frequently ampicillin resistant and Fluoroquinolone-resistant E. faecalis were more highly resistant to gentamicin. Conclusions: Although intrinsically poorly susceptible to fluoroquinolones, gut populations of enterococci are highly impacted both quantitatively and qualitatively by ciprofloxacin.